Considering ecological flow in multi-objective operation of cascade reservoir systems under climate variability with different hydrological periods. (1st May 2022) - Lu, Xiaorong; Wang, Xuelei; Ban, Xuan; Singh, Vijay P.
Abstract: The trade-off between ecological and socioeconomic benefits in the reservoir operation has become a focus issue in the watershed water resource management. However, finding a suitable reservoir ecological operation scheme in the multi-objective cascade reservoir systems remains unclear. At present, most ecological operation models are designed on the basis of water quantity balance, neglecting the dynamic variability of the hydrological process. This study proposed a multi-objective ecological operation system, which coupled a two-dimensional hydrodynamic model with a rainfall–runoff model, and integrated the ecological operation scheme into the hydrodynamic simulation system considering ecological flow. Moreover, the applicability of the operation scheme under climate variability with different hydrological periods was evaluated. Results indicated that multi-reservoir joint operation had the largest effect in normal years; the variation in the monthly hydrological magnitude, extreme events and their duration, temporal change and frequency of streamflow were significantly reduced after reservoir ecological operation. The SAM0-UNICON model performed better than the two other climate models, the ecological deficit (ED) under the Representative Concentration Pathway (RCP) 8.5 climate change scenario was larger than other scenarios with different operation schemes. Future climate change will have a larger impact on discharge change in the wet season than in other hydrological periods. This study emphasises the comprehensive application of the hydrological and hydrodynamic methods, which is of considerable importance for decision-making in basin water resource management and reservoir regulation. Graphical abstract: Image 1 Highlights: An ecologically oriented operation strategy for a multi-reservoir system. Developed a hydrodynamic model (HD) coupled with a rainfall-runoff model (NAM). A simulation system to alleviate the influence of reservoirs on river ecosystem. Reservoir ecological operation for adaptation to climate change.